2019
DOI: 10.1002/ccd.28147
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular geometry predicts optimal response to percutaneous mitral repair via MitraClip: Integrated assessment by two‐ and three‐dimensional echocardiography

Abstract: Objectives: To assess impact of left ventricular (LV) chamber remodeling on MitraClip (MClp) response. Background: MitraClip (MClp) is the sole percutaneous therapy approved for mitral regurgitation (MR) but response varies. LV dilation affects mitral coaptation; determinants of MClp response are uncertain. Methods: LV and mitral geometry were quantified on pre- and post-procedure two-dimensional (2D) transthoracic echocardiography (TTE) and intra-procedural three-dimensional (3D) transesophageal echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Furthermore, recent evidence shows that isolated atrial dilatation in the context of permanent atrial fibrillation and heart failure with preserved ejection fraction might itself cause secondary MR. Due to the distinct patho‐morphology of MR in atrial remodelling, technical amenability for TMVR might be different from MR resulting from ventricular remodelling, and efficacy of TMVR in these patients has not been examined . Finally, LA enlargement might affect procedural handling of the device and technical efficacy due to distorted septum to mitral valve relation . On the other hand, very small left atria might also impair handling of the device during manoeuvring and grasping.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent evidence shows that isolated atrial dilatation in the context of permanent atrial fibrillation and heart failure with preserved ejection fraction might itself cause secondary MR. Due to the distinct patho‐morphology of MR in atrial remodelling, technical amenability for TMVR might be different from MR resulting from ventricular remodelling, and efficacy of TMVR in these patients has not been examined . Finally, LA enlargement might affect procedural handling of the device and technical efficacy due to distorted septum to mitral valve relation . On the other hand, very small left atria might also impair handling of the device during manoeuvring and grasping.…”
Section: Introductionmentioning
confidence: 99%
“…LV chamber size was over 25% larger in MITRA-FR vs. COAPT patients, paralleling a > 3-fold increase in recurrent severe MR: MITRA-FR reported MitraClip to have no impact on outcomes, whereas MR reduction in COAPT was accompanied by heart failure and mortality benefit. As further evidence of the importance of LV remodeling as a determinant of MitraClip response, prior research from our group (encompassing 67 patients included in the current cohort) showed increased LV size to be associated with risk for sub-optimal MitraClip response (>mild MR): [5] However, the relative utility of 2D and 3D derived mitral annular size independent of LV chamber volume, impact of the device on annular remodeling, as well as intra-procedural annular remodeling as a determinant of therapeutic response were not tested – providing key rationales for the current study.…”
Section: Discussionmentioning
confidence: 77%
“…MitraClip is intended to reduce MR via focal leaflet coaptation. However, prior echo studies by our group and others have shown increased left ventricular (LV) size to augment risk for recurrent MR after MitraClip implantation [5], supporting the notion that remodeling indices beyond mitral valve anatomy impact therapeutic response. It is also possible that the device itself contributes to risk for MR recurrence.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lubos et al found that effective regurgitant orifice area >70.8 mm 2 and mitral valve area ≤ 3.0 cm 2 independently predicted clip failure (defined by aborted procedure or inability to reduce MR to ≤ 2+ in severity) (33). A recent paper studying treatment of degenerative MR suggested that higher baseline left-ventricular end-diastolic diameter and mitral annular diameter predict greater than mild residual MR after mitraclip (17). In current clinical practice, absolute anatomic limitations are very few (18).…”
Section: Mitraclipmentioning
confidence: 99%